Utilization of intraoperative contrast-enhanced ultrasound in the treatment of complex endoleaks - Mackenzie Snyder, MD; Hannah Pambianchi, BA; Megan Lenihan, MD; David Spinosa, MD; Kendal M. Endicott, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Contrast-enhanced ultrasound (CEUS) is an imaging adjunct utilized at select centers for the detection of occult abdominal aortic endograft endoleaks. This report details three cases utilizing intraoperative CEUS to aid in the treatment of clinically significant endoleaks. In particular, CEUS provided real-time feedback regarding treatment success. This approach also allowed for minimalization of iodinated contrast in a patient with advanced renal disease and localization to guide direct needle puncture. CEUS is a powerful imaging modality that can aid in the identification and treatment execution of difficult endoleaks.